Light‐Induced Cold Marangoni Flow for Microswarm Actuation: From Intelligent Behaviors to Collective Drug Delivery. Issue 12 (18th September 2022) - Shi, Yang; Wang, Danning; Xiao, Yuqing; Pan, Ting; Lu, Dengyun; Zhu, Guoshuai; Xiong, Jianyun; Li, Baojun; Xin, Hongbao
Abstract: Microswarms have shown great potential in biomedical applications at small scales due to their features of wireless actuation and collective microrobotic behaviors. However, actuation of microswarms with strong universality and intelligent biomimetic behaviors is always a great challenge. Here, photothermal damage‐free actuation of an intelligent microswarm based on light‐induced cold Marangoni flow (CMF) is reported, along with collective drug delivery and targeted cell chemotherapy. This microswarm actuation shows strong universality and high controllability for both abiotic particles and living materials. Importantly, this microswarm exhibits intelligent biomimetic behaviors, such as collective migration, size‐based self‐organization, and group rejection, due to the synergy between cold flow with individual agents. The distinctive photothermal isolation capability of CMF ensures the microswarm to perform photothermal damage‐free biomedical tasks such as collective gene delivery and targeted single‐cell chemotherapy. This light‐induced CMF provides an optical strategy for photothermal damage‐free actuation of intelligent biomimetic microswarm robots, with great promises to perform many collective and cognitive tasks in biomedical applications such as cooperative grasping, collective drug delivery, and precise chemotherapy. Abstract : Light‐induced cold Marangoni flow (CMF) technique is applied for photothermal damage‐free actuation of intelligent microrobotic swarms with strong universality and intelligent behaviors. The distinctive photothermal isolation capability of CMF ensures the microrobotic swarm to execute multiple biomedical tasks such as collective gene delivery and targeted cell chemotherapy.